COVID–Activated Emergency Scaling of Anesthesiology Responsibilities Intensive Care Unit. (August 2020) - Verdiner, Ricardo E.; Choukalas, Christopher G.; Siddiqui, Shahla; Stahl, David L.; Galvagno, Samuel M.; Jabaley, Craig S.; Bartz, Raquel R.; Lane-Fall, Meghan; Goff, Kristina L.; Sreedharan, Roshni; Bennett, Suzanne; Williams, George W.; et al.
Abstract : In response to the rapidly evolving coronavirus disease 2019 (COVID-19) pandemic and the potential need for physicians to provide critical care services, the American Society of Anesthesiologists (ASA) has collaborated with the Society of Critical Care Anesthesiologists (SOCCA), the Society of Critical Care Medicine (SCCM), and the Anesthesia Patient Safety Foundation (APSF) to develop the COVID-Activated Emergency Scaling of Anesthesiology Responsibilities (CAESAR) Intensive Care Unit (ICU) workgroup. CAESAR-ICU is designed and written for the practicing general anesthesiologist and should serve as a primer to enable an anesthesiologist to provide limited bedside critical care services.